Analysis of the effect of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio) acetate high doses on brain tissue - Safonov, A. A.; Gotsulya, A. S.; Shcherbyna, R. O.; Panasenko, O. I.; Сафонов, Андрій Андрійович; Гоцуля, Андрій Сергійович; Щербина, Роман Олександрович; Панасенко, Олександр Іванович (My University, 2025)
The aim of the study is to analyze the effect of high doses of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio) acetate (ASP) on brain tissue. Material and methods. The effect of ASP high doses (1000 mg/kg and 5000 mg/kg) was studied on white outbred rats. The substance was administered intragastrically dissolved in purified water using a special metal probe. The brain tissue was fixed in a 10% formaldehyde solution for subsequent histological examination, dehydrated in alcohols of increasing concentrations, and embedded in paraffin. Results. Analyzing the effect of different doses of ASP on brain tissue, it can be concluded that at 1000 mg/kg, vacuolar cytoplasmic degeneration is detected in many neurons and cells without nuclei are observed. This is indicated by histological evidence of selective neuronal death. At the same time, the capillary system is preserved. Partial chromatolysis of Purkinje cells is observed in the cerebellum, the layering is preserved. Against the background of moderate interstitial edema of the brain selective neuronal death with the formation of collapsed (eosinophilic) neurons is observed at 5000 mg/kg. A dose 10 times higher than effective dose (1000 mg/kg) leads to changes in the histological structure of organ tissues. The maximum argued dose of the fourth toxicity class of 5000 mg/kg also causes more serious changes in the structure of organ tissues. Стаття присвячена дослідженню тканин мозку у разі введення високих доз (1000 мг/кг і 5000 мг/кг) 2-((4-аміно-5-(тіофен-2- ілметил)-4Н-1,2,4-триазол-3-іл)тіо)ацетату перорально за допомогою зонду. Доза в 10 разів більша за ефективну дозу (100 мг/кг – щури) – 1000 мг/кг уже призводить до змін гістологічної структури тканин органів. Максимальна аргументована доза четвертого класу токсичності 5000 мг/кг також викликає серйозніші зміни у структурі тканин органів. Таким чином, наше дослідження дало докази зміненої гістологічної архітектури тканини мозку.
Аналіз впливу високих доз 2-((4-аміно-5-(тіофен-2-ілметил)-4н-1,2,4-триазол-3-іл)тіо) ацетату на тканину мозку
Keywords: 1,2,4-triazole; brain tissue; toxic effect; 1,2,4-триазол; мозкова тканина; токсична дія